LIVING AGAINST THE CLOCK: A NARRATIVE REVIEW OF SOCIAL JETLAG, HEALTH CONSEQUENCES, AND MODIFIABLE RISK FACTORS - Katarzyna Szewczyk; Wirginia Bertman; Klaudia Romejko; Kamil Borysewicz; Zuzanna Kępczyńska; Wiktor Kubik; Bartłomiej Czarnecki; Barbara Kujawa; Jan Nowak; Bartosz Zwoliński; Natalia Kołdej; Kacper Sukiennicki (International Journal of Innovative Technologies in Social Science, 2025)
Objective: This review examines the prevalence, causes, and health impacts of social jetlag (SJL), a chronic circadian misalignment arising from mismatches between biological sleep-wake timing and socially imposed schedules. It synthesizes contemporary knowledge on SJL’s epidemiology, measurement, biological mechanisms, and public health relevance.Background: SJL has become increasingly common among adolescents and shift workers, driven by factors such as early school start times, rotating work shifts, and increased nighttime digital screen use. These influences disrupt regular sleep patterns, resulting in persistent conflicts with endogenous circadian rhythms.Methods: A narrative review was conducted including peer-reviewed studies from 2015 to 2025, with one foundational exception (Wittmann et al., 2006). Databases searched were PubMed, Scopus, Web of Science, and Google Scholar. Studies were included based on relevance to SJL, circadian misalignment, and health outcomes in humans.Results: Literature indicates SJL is linked to elevated cardiometabolic risks, including type 2 diabetes, obesity, and systemic inflammation. In adolescents and young adults, SJL is also associated with poor sleep quality, increased daytime sleepiness, and higher depressive symptom rates. Objective measures, like actigraphy and biomarkers, support these findings. Social and institutional timing structures are modifiable contributors to SJL.Discussion: SJL is a measurable and harmful circadian disruption with short-term effects such as fatigue and cognitive impairments and long-term impacts including metabolic and mental health disorders. Despite evidence growth, longitudinal and intervention research remains limited, hindering population-level mitigation strategies.Conclusion: SJL is a common, modifiable circadian health issue linked to broad physiological and psychological risks. Interventions like delaying school starts and chronotype-personalized shift schedules could alleviate SJL’s burden and improve long-term public health.